If it's not what You are looking for type in the equation solver your own equation and let us solve it.
p in (-oo:+oo)
p-18 = -6*(23/3) // + -6*(23/3)
p-(-6*(23/3))-18 = 0
p-18+46 = 0
p+28 = 0 // - 28
p = -28
p = -28
| 0=y-(-2) | | 1=-1*y | | y^3-y^2-y+1= | | 2-(-y)=0 | | px+18=qx | | 6g^2-7g-5=0 | | -8+a=-24 | | 0.1x+0.9(10-x)=5 | | 8=y-(-1) | | 5d^2-20d-105=0 | | t^2=12-4t | | 5/7(-1x+6)=60/7 | | -34x^2+34x=0 | | 3m^2+33m+30=0 | | 6(-1x+5)=90 | | -16x^2+34x=0 | | 3/5-3x=4x-312/5 | | 14y^2-14y+5= | | 6r^2+34r+20=0 | | 100/50=(7^2)+5y | | y=2/3(-3)-4 | | 7x-8y=10 | | 2y+4-4y=y+16 | | -3p^2+11p+20=0 | | 36=18*6+b | | -2y+4-4y=y+16 | | 0=-3/7x-3 | | 4/9r=12 | | -1-5x=14x-14 | | 12=-.9a | | 36=44/9*6+b | | y/7+10.1=-1.1 |